Será a educaçãoa culpada? - Luiza Cortesão (EccoS – Revista Científica)
Two different kinds of negative criticism concerning the role of school in society are analysed in this paper. Some features of these quite opposite critics are described and related with different economic and political contexts where they were (and are) produced